Global multisensory reorganization after vestibular brain stem stroke. Issue 10 (28th August 2020) - Conrad, Julian; Habs, Maximilian; Boegle, Rainer; Ertl, Matthias; Kirsch, Valerie; Stefanova‐Brostek, Iskra; Eren, Ozan; Becker‐Bense, Sandra; Stephan, Thomas; Wollenweber, Frank; Duering, Marco; zu Eulenburg, Peter; et al.
Abstract: Objective: Patients with acute central vestibular syndrome suffer from vertigo, spontaneous nystagmus, postural instability with lateral falls, and tilts of visual vertical. Usually, these symptoms compensate within months. The mechanisms of compensation in vestibular infarcts are yet unclear. This study focused on structural changes in gray and white matter volume that accompany clinical compensation. Methods: We studied patients with acute unilateral brain stem infarcts prospectively over 6 months. Structural changes were compared between the acute phase and follow‐up with a group of healthy controls using voxel‐based morphometry. Results: Restitution of vestibular function following brain stem infarcts was accompanied by downstream structural changes in multisensory cortical areas. The changes depended on the location of the infarct along the vestibular pathways in patients with pathological tilts of the SVV and on the quality of the vestibular percept (rotatory vs graviceptive) in patients with pontomedullary infarcts. Patients with pontomedullary infarcts with vertigo or spontaneous nystagmus showed volumetric increases in vestibular parietal opercular multisensory and (retro‐) insular areas with right‐sided preference. Compensation of graviceptive deficits was accompanied by adaptive changes in multiple multisensory vestibular areas in both hemispheres in lower brain stem infarcts and by additional changes in the motor system in upper brain stem infarcts. Interpretation: This study demonstrates multisensory neuroplasticity in both hemispheres along with the clinical compensation of vestibular deficits following unilateral brain stem infarcts. The data further solidify the concept of a right‐hemispheric specialization for core vestibular processing. The identification of cortical structures involved in central compensation could serve as a platform to launch novel rehabilitative treatments such as transcranial stimulations.